Analisis Perubahan Karakteristik Aliran Fluida sekitar SPAR-3VP Terhadap Variasi Kecepatan Aliran di Kondisi Ekstrim - Galy Rakaziwi; Fuad Mahfud Assidiq (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
This research discusses the SPAR offshore wind turbine, a floating foundation turbine used for wind power generation in the deep sea. SPARs are designed with a large-diameter vertical floating cylinder weighted at its lower end, creating a structure that is less responsive to wind, waves, and currents. SPAR foundations have advantages in deep water due to their low center of mass, simple ballast stabilization, and high stability. The purpose of this research is to gain a deeper understanding of the fluid flow occurring around the SPAR, which impacts the performance and stability of the offshore wind turbine. This research will focus on CFD (computational fluid dynamics)-based numerical modeling analysis with the help of 3D analysis software ANSYS by considering several variations of fluid flow velocity to identify the pressure, velocity, and changes in fluid flow around the SPAR. The results of this study are expected to help in reducing the risk of SPAR foundation damage, improving turbine stability, and overall increasing the efficiency of offshore wind energy generation. This research has positive implications for reducing the environmental impact of energy generation compared to traditional fossil fuel sources.